Psychoeducation As A Strategy To Improve Interpersonal Competence Among Psychology Laboratory Assistants - Izzah, Lailatul; Eva Yuliza; Muharrani; Renny Rahmalia; Kurniawan, Willytiyo; Hamdi, Raspan; Fitriah, Nur (Jurnal Masyarakat Mengabdi, 2025)
Psychology laboratory assistants play a strategic role in supporting the student learning process, not only as facilitators of practicum activities but also as mentors and role models. However, initial observations revealed that interpersonal competencies, particularly in effective communication, teamwork, conflict management, empathy, and emotional intelligence, remain suboptimal. This community service activity aimed to improve the interpersonal competencies of laboratory assistants through psychoeducation based on experiential learning. The methods employed included interactive lectures, brainstorming, ice breaking, games, role play, and reflective discussions. The participants were 33 psychology laboratory assistants. The results indicated an increase in participants’ theoretical understanding, practical skills, and reflective awareness regarding the importance of interpersonal competence in their roles. Participants also demonstrated personal commitment to applying interpersonal skills in laboratory activities. Thus, psychoeducation proved effective as a strategy to strengthen the capacity of laboratory assistants in creating a conducive, professional, and collaborative learning environment.